2023
DOI: 10.21203/rs.3.rs-2426862/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relationship Between Attendance of at Least Four Antenatal Care Visits and Facility Delivery

Abstract: Background The current global situation is such that 340,000 women still die annually of avoidable maternal health-related complications. Recent statistics in Uganda indicate that maternal deaths among women of age 15 – 49 years are 18% translating to a maternal mortality ratio of 336 deaths per 100,000 live births. Moreover, at least 26% of live deliveries are not attended to by professional practitioners, and 27% are not delivered at a health facility. Additionally, 40% of the last Uganda Demographic and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Distance is the degree of ease with which people can reach an object, service, or environment. In another sense, distance is a measure of the ease of a location to be reached from other locations via the transportation system [11] . In this research, what is meant by affordability or accessibility is a combination of distance, travel time, level of ease, and difficulty for mothers to obtain birth assistance facilities by health workers.…”
Section: Discussionmentioning
confidence: 99%
“…Distance is the degree of ease with which people can reach an object, service, or environment. In another sense, distance is a measure of the ease of a location to be reached from other locations via the transportation system [11] . In this research, what is meant by affordability or accessibility is a combination of distance, travel time, level of ease, and difficulty for mothers to obtain birth assistance facilities by health workers.…”
Section: Discussionmentioning
confidence: 99%
“…In assessing the relationship between attendance of at least four ANC visits and skilled birth attendance, Nkeeto found that attending at least four ANC visits was a positive predictor of skilled birth attendance. 21 Wanjohi et al in a study on the predictors of birth preparedness in Laikipia county, Kenya, concluded that practice of birth preparedness is an integral endeavour towards total eradication of unskilled delivery. 22…”
Section: Maternal Health Related Factors Of the Respondents In Kitui ...mentioning
confidence: 99%